Long cycle‐life aqueous Zn battery enabled by facile carbon nanotube coating on Cu current collector - Beom‐Keun Cho; Sung‐Ho Huh; So Hee Kim; Seungho Yu; Jong‐Seong Bae; Jung‐Keun Yoo; Seung‐Ho Yu (Carbon Energy, 2024)
Abstract As an alternative to Li‐ion batteries, aqueous Zn batteries have gained attention due to the abundance of Zn metal, low reduction potential (–0.76 V vs. standard hydrogen electrode), and high theoretical capacity (820 mAh g–1) of multivalent Zn2+ ion. However, the growth of Zn dendrites and the formation of irreversible surface reaction byproducts pose challenges for ensuring a long battery lifespan and commercialization. Herein, the Cu foil coated with a single‐walled carbon nanotube (SWCNT) layer using a facile doctor blade casting method is utilized. The SWCNT‐coated Cu foil demonstrates a significantly longer battery lifespan compared to the bare Cu in the half‐cell tests. Through operando optical microscopy imaging, we are able to provide intuitive evidence that Zn deposition occurs between the carbon nanotube (CNT) coating and Cu substrate, in agreement with the computational results. Also, with various imaging techniques, the flat morphology and homogeneous distribution of Zn beneath the SWCNT layer are demonstrated. In addition, the full‐cell using CNT‐coated Cu exhibits a long cycle life compared to the control group, thereby demonstrating improved electrochemical performance with limited Zn for the cycling process.